An overview of sustainable bioenergy potential in Algeria. (May 2017) - Akbi, Amine; Saber, Meryem; Aziza, Majda; Yassaa, Noureddine
Abstract: Owing to its important potential, bioenergy has been integrated in the recent ambitious renewable energy program of Algeria. As biomass sources are tremendous and so diversified, bioenergy production can take many and varied forms. Assessment of national biomass potential is essential for the development of bioenergy sector in Algeria. This paper focuses on identifying domestic sustainable biomass resources with emphasis on energy production. The energy potential of waste generated by different sectors (urban, industrial …) is investigated. The resulted outcome showed that urban waste are the prominent fermentable resource and can produce as much as 1685 GWh through the anaerobic digestion process. Other agribusiness resources, although at lower extent, can also contribute to the global bioenergy potential in Algeria. The estimated energy capable to be generated from the investigated biomass resources can cover the annual consumption of more than one million inhabitants.